Photocurable ink for automotive interior applications and glass article provided with same

JP2025505094APending Publication Date: 2025-02-21CORNING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024539818
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-01-13
Publication Date
2025-02-21

Smart Images

  • Figure 2025505094000001_ABST
    Figure 2025505094000001_ABST
Patent Text Reader

Abstract

Disclosed herein is a glass article comprising a glass substrate having a major surface and an opaque layer disposed on the major surface. The opaque layer is made from a photocurable ink including at least 10% by weight pigment. The opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater. The opaque layer, after curing by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED"), exhibits (a) a pencil hardness of 3H or greater, as measured according to ASTM 3363, and (b) adhesion to the glass substrate of 4B or greater, as measured according to ASTM 3359, after exposure to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Priority

[0001] This application claims the benefit of priority under 35 U.S.C. § 119 of U.S. Provisional Patent Application No. 63 / 304,732, filed January 31, 2022, and U.S. Provisional Patent Application No. 63 / 393,532, filed July 29, 2022, the contents of which are relied upon and incorporated herein by reference in their entireties. [Technical field]

[0002] The present disclosure relates to photocurable inks and glass articles comprising same for interior automotive display applications. [Background technology]

[0003] Automotive interiors may include a display with a display cover glass. A display module (e.g., a liquid crystal display ("LCD") module, an organic light emitting diode ("OLED") display module, or other suitable type of display module) may be laminated to or otherwise integrated with the cover glass such that the cover glass protects the display module and / or provides one or more performance enhancing attributes (e.g., anti-glare or anti-reflective properties) to the display module. Decorative inks may be applied to certain areas of the cover glass to hide various components of the display (e.g., electrical connections and mechanical bonds) and / or to give the display a uniform appearance when the display is turned off. Some existing inks used to decorate display cover glasses may have various deficiencies that make them unsuitable for automotive interior applications. For example, some existing inks may be applied by a screen printing process, which requires multiple layers to provide the desired optical density and may have a relatively low production throughput. Other existing inks (e.g., UV curable inks) may fail to provide the desired optical density per unit thickness and / or fail to provide adequate adhesion to the cover glass either after environmental testing associated with the variable environmental conditions (e.g., with respect to temperature and humidity) to which the components are exposed. Summary of the Invention [Problem to be solved by the invention]

[0004] Therefore, there is a need for alternative inks that meet the requirements associated with interior automotive display applications. [Means for solving the problem]

[0005] One embodiment relates to a glass article comprising: a glass substrate having a first major surface and a second major surface opposite the first major surface; and an opaque layer disposed on the second major surface, the opaque layer made from a photocurable ink including at least 10% by weight pigment, the opaque layer having a thickness of 25 μm or less and an optical density of 4.0 or greater, the opaque layer, after being cured by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED"), exhibits a pencil hardness of 3H or greater, as measured in accordance with ASTM 3363, and adhesion to the glass substrate of 4B or greater, as measured in accordance with ASTM 3359, after being exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0006] Another embodiment includes a display for a vehicle interior system comprising: a glass substrate having a first major surface and a second major surface opposite the first major surface; an opaque layer disposed on the second major surface, the opaque layer made from a photocurable ink including at least 10% by weight pigment; and a display panel disposed on the second major surface, the opaque layer disposed in a peripheral region of the second major surface and spanning an edge of the display panel, the opaque layer having a thickness of 25 μm or less and an optical density of 4.0 or greater, and the opaque layer, after curing by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED"), exhibits a pencil hardness of 3H or greater, as measured in accordance with ASTM 3363, and adhesion to the glass substrate of 4B or greater, as measured in accordance with ASTM 3359, when exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0007] Another embodiment relates to a method of manufacturing a glass article comprising: depositing a photocurable ink on a major surface of a glass substrate using an inkjet printhead at a deposition temperature of 65° C. or less, wherein during deposition, the photocurable ink has a viscosity of less than 25 cP, the photocurable ink comprising at least 10% by weight of a pigment and at least 50% by weight of a reactive monomer; and curing the photocurable ink on the major surface by exposing the photocurable ink to an ultraviolet ("UV") light emitting diode ("LED") generated curing light to form an opaque layer, the curing light having a bandwidth of 30 nm or less, wherein the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater, and wherein the opaque layer exhibits a pencil hardness of 3H or greater, as measured according to ASTM 3363, and adhesion to the glass substrate of 4B or greater, as measured according to ASTM 3359, when exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0008] It is to be understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a further understanding, and are incorporated in and constitute a part of this specification. The drawings illustrate one or more embodiment(s), and together with the description, serve to explain the principles and operation of the various embodiments. [Brief description of the drawings]

[0009] The accompanying drawings, which are incorporated in and form a part of this specification, illustrate several aspects of the invention and, together with the description, serve to explain the principles of the invention. [Figure 1] FIG. 1 is a perspective view of a vehicle cabin with a vehicle cabin system having a display in accordance with one or more embodiments of the present disclosure. [Diagram 2] 2 is a cross-sectional view of a display of a cabin system taken through line 2-2 shown in FIG. 1 in accordance with one or more embodiments of the present disclosure. [Diagram 3]1 is a flow diagram of a method of forming a glass article having an opaque layer according to one or more embodiments of the present disclosure. [Figure 4] 1 is a plot of measured optical density as a function of opaque layer thickness for Examples 1-3, according to one or more embodiments of the present disclosure. [Diagram 5] Photograph of a sample formed according to Example 2 after being subjected to a cross-hatch adhesion test, according to one or more embodiments of the present disclosure. [Figure 6A] Photograph of a sample coated with a first commercial UV curable ink after high temperature and humidity testing according to one or more embodiments of the present disclosure. [Figure 6B] Photograph of a sample coated with a second commercially available UV-curable ink after testing at elevated temperature and humidity, according to one or more embodiments of the present disclosure. [Figure 7] 1 is a plot showing optical density of samples as a function of thickness of an opaque layer formed according to Example 5, in accordance with one or more embodiments of the present disclosure. [Figure 8] Photograph of a sample formed according to Example 5 after being subjected to a crosshatch adhesion test, according to one or more embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Referring broadly to the drawings, described herein are photocurable inks that may be used to form opaque layers on display cover glasses by a high-throughput curing process. Once the photocurable inks are cured, the opaque layers may have relatively high adhesion to glass and high optical density per unit thickness while eliminating certain solvents that tend to be environmentally harmful. In embodiments, for example, the photocurable inks described herein may be cured into opaque layers that provide an optical density of 4 or greater (e.g., 5 or greater) while having a thickness of less than 25 μm (e.g., 20 μm or less, 15 μm or less, 10 μm or less). The photocurable inks may also be cured using light-emitting diode ("LED") light sources that have relatively narrow ultraviolet ("UV") spectral output (e.g., 365±10 nm, 385±10 nm, 395±10 nm, 405±10 nm), improving production efficiency. Additionally, the photocurable inks described herein may be compatible with commercially available inkjet printing processes (e.g., having an uncured viscosity of less than 25 cP at temperatures of 60° C. or less) to facilitate relatively low-cost, high-throughput manufacturing processes. All of the photocurable inks described herein may provide each of the beneficial properties described above while exhibiting reliable adhesion to coverglass when subjected to environmental testing. Certain ink compositions according to the present disclosure may exhibit adhesion to coverglass of 4B or greater when subjected to a cross-hatch tape test according to ASTM 3359, all of which are incorporated herein by reference.

[0011] In embodiments, the photocurable ink of the present disclosure includes a pigment dispersant, an optional adhesion promoter, a binder solution, a multifunctional monomer, and a photoinitiator package. The pigment dispersant includes 20% to 50% by weight of a suitable pigment (e.g., a carbon black pigment) or a suitable mixture of pigments and 50 to 80% by weight of a first reactive monomer (e.g., a suitable acrylate monomer such as neopentyl glycol diacrylate or trimethylolpropane triacrylate). The pigment may comprise 10% or more by weight (e.g., 20% or more by weight) of the ink composition to promote an ink having a relatively high optical density (e.g., 4 or more, 5 or more) at a relatively small thickness (e.g., 25 μm or less after curing). The first reactive monomer may be present in an amount of 40% or more and 60% or less by weight of the photocurable ink composition. The adhesion promoter, if included, may comprise between 10% and 20% by weight of the ink composition and may include a monofunctional monomer to improve adhesion to the cover glass. For example, the adhesion promoter may include 2-hydroxyethyl acrylate (2-HEA) monomer. The binder solution may include a suitable epoxy resin to adjust the adhesion and surface hardness of the cured opaque layer. The epoxy resin may comprise less than 5% by weight of the ink composition. In embodiments, the binder solution includes a suitable acrylate monomer as a reactive diluent in addition to the epoxy resin. The photocurable ink may also include a multifunctional monomer to achieve a relatively high crosslink density (e.g., to promote high surface hardness). The photoinitiator package may include one or more suitable photoinitiators to promote curing using ultraviolet LEDs. In embodiments, the photoinitiator package includes a Norrish Type I photoinitiator and a Norrish Type II photoinitiator to induce rapid photopolymerization of the ink composition. The total weight percent of the photoinitiators in the package may comprise up to 10% by weight of the ink composition. In embodiments, the Type I photoinitiator has a concentration greater than twice the concentration of the Type II photoinitiator to promote photopolymerization. The photocurable inks of the present disclosure may also include less than 0.5% by weight (e.g., less than 0.1% by weight) of a suitable polymerization inhibitor for ease of transportation and storage.

[0012] The photocurable inks of the present disclosure may also meet various environmental standards. For example, in embodiments, the photocurable inks described herein may contain less than 10% by weight volatile organics and therefore may meet GB 35807-2020, entitled "Limits of Volatile Organic Compounds (VOCs) in Printing Ink," which is incorporated herein in its entirety by reference. Additionally, the photocurable inks of the present disclosure may be free of halogenated hydrocarbons and free of solvents identified by CAS Registry Numbers in Table 1.

[0013] [Table 1]

[0014] Such solvents are known to have potentially harmful effects on the environment and / or human health. Some existing photocurable inks include the solvents listed in Table 1 to provide a UV curable ink with a relatively high optical density compatible with inkjet printing. The photocurable inks of the present disclosure provide such favorable attributes without such harmful solvents. The photocurable inks of the present disclosure provide an uncured viscosity suitable for inkjet printing without the addition of harmful solvents, and therefore can be used for relatively high throughput (e.g., 20 m) with commercially available printheads. 2 / hour over 30m 2 / hour over 40m 2 / hour over 50m 2 The inkjet printing process is beneficially compatible with chemically strengthened cover glass, unlike certain other inks based on ceramic frits that require relatively high curing temperatures.

[0015] In embodiments, the photocurable inks described herein may be tailored to meet specific appearance requirements related to design needs. For example, a cover glass with an opaque layer composed of the photocurable inks described herein may meet any of the black mask color targets in Table 2.

[0016] [Table 2]

[0017] In embodiments, an opaque layer constructed using the photocurable inks described herein may meet any combination of values ​​contained in Table 2 that are within the tolerances outlined in Table 3 below.

[0018] [Table 3]

[0019] As shown in Tables 2 and 3, cover glasses containing the photocurable inks described herein generally have a CIELAB L of 30 or less (29 or less, 28 or less, 27 or less, 25 or less, 25 or less) when illuminated with a CIE D65 light source at an angle of incidence of 10° when viewed on the uncoated surface of the cover glass (e.g., from the side of the glass opposite the side on which the display is located). * CIELAB a value, greater than or equal to -0.05 and less than or equal to 0.15 * value (including the reflectance component), and CIELAB b less than or equal to -0.1 and greater than or equal to -0.3 * If the specular component is eliminated, the cover glass will have a CIELAB L value of 1 or less. * CIELAB a values ​​and magnitudes less than or equal to 0.1 * Value and b * Areas of the cover glass coated with the light curable inks described herein may exhibit a dark, neutral appearance to facilitate hiding various components from view.

[0020] The photocurable inks of the present disclosure may also be used to construct an opaque layer on a glass article that exhibits favorable reliability test results when compared to certain existing photocurable inks. Automotive interior components are exposed to highly variable environmental conditions (e.g., with respect to temperature and relative humidity). In embodiments, the opaque layer may meet one or more of the following criteria when subjected to the reliability tests outlined in Table 4:

[0021] [Table 4]

[0022] Research has revealed that certain existing UV curable inkjet compatible inks crack or otherwise fail when exposed to such test conditions, rendering those inks unsuitable for certain automotive interior applications. For example, certain existing inks have been found to shrink and / or crack when Test B contained in Table 4 above is performed, whereas the photocurable inks described herein meet the test criteria contained in Table 4.

[0023] The photocurable inks described herein, in addition to meeting the reliability test requirements described above, may meet the additional requirements given in Table 5 that make them suitable for certain commercially available ink jet printers.

[0024] [Table 5]

[0025] The photocurable inks described herein may also exhibit a pencil hardness of 3H or greater when measured with a pencil at a 45° angle with a mass of 750 g according to ASTM 3363, entitled "Standard Test Method for Film Hardness by Pencil Test," which is incorporated herein in its entirety, after being cured with a narrowband UV LED light source emitting a narrowband (e.g., 20 nm or less bandwidth, 30 nm or less bandwidth) curing light. The use of such UV LEDs saves space and cost and is less environmentally harmful when compared to certain existing UV curing lamps. Certain existing UV curable inks, when meeting the optical density requirements described herein, may not cure sufficiently to have such pencil hardness due to ink opacity inhibiting curing. The photoinitiators of the inks described herein may be selected to facilitate curing using UV LEDs while still meeting the pencil hardness and optical density requirements described herein.

[0026] Thus, the photocurable inks described herein provide a relatively high optical density per unit thickness to promote their effectiveness as black matrix layers in displays, while being compatible with high throughput inkjet printing processes and also meeting the stringent reliability testing requirements associated with interior automotive displays. The photocurable inks described herein provide cost savings in the manufacture of cover glass for displays, while still providing a reliable opaque layer that has been demonstrated to provide consistent color performance over the life of the component.

[0027] FIG. 1 illustrates a vehicle cabin 1000 with three different vehicle cabin systems 100, 200, 300 according to example embodiments. Vehicle cabin system 100 includes a center console base 110 having a curved surface 120 that includes a display 130. Vehicle cabin system 200 includes a dashboard base 210 having a curved surface 220 that includes a display 230. Dashboard base 210 typically includes an instrument panel 215 that may also include a curved display. Vehicle cabin system 300 includes a dashboard handle base 310 having a curved surface 320 and a display 330. In one or more embodiments, the vehicle cabin system may include a base that is an armrest, pillar, seat back, floor panel, headrest, door panel, or any part of the interior of the vehicle that includes a curved surface. In an embodiment, display 130, 230, 330 is flat and includes a cover glass having a flat major surface. In embodiments, one or more of the displays 130, 230, 330 are curved, and the curved display may include a curved cover glass that may be hot or cold formed to have such a curvature. For example, such an embodiment may include an opaque layer formed from a photocurable ink as described herein disposed on a cold-formed glass substrate.Such cold forming may include any of the techniques described in U.S. Patent Application Publication No. 2019 / 0329531 A1, entitled "Laminating thin strengthened glass to curved molded plastic surface for decorative and display cover application," U.S. Patent Application Publication No. 2019 / 0315648 A1, entitled "Cold-formed glass article and assembly process thereof," U.S. Patent Application Publication No. 2019 / 0012033 A1, entitled "Vehicle interior systems having a curved cover glass and a display or touch panel and methods for forming the same," and U.S. Patent Application No. 17 / 214124, entitled "Curved glass constructions and methods for forming same," all of which are incorporated herein by reference.

[0028] The glass article embodiments described herein can be used in any or all of the cabin systems 100, 200, and 300. Although FIG. 1 illustrates the interior of an automobile, the various embodiments of the cabin system can be incorporated into any type of vehicle, such as trains, automobiles (e.g., cars, trucks, buses, etc.), marine vehicles (boats, ships, submarines, etc.), and aircraft (e.g., drones, planes, jets, helicopters, etc.), including all human-operated, semi-autonomous, and fully autonomous vehicles. Additionally, while the description herein primarily relates to the use of glass articles in vehicle displays, it should be understood that the various embodiments described herein can be used in any type of display application.

[0029] Figure 2 illustrates a schematic cross-sectional view of a display 230 taken through line 2-2 in Figure 1 according to an example embodiment in which the display 230 is flat. While Figure 2 illustrates one example of a display 230, it should be understood that the displays 130, 330 described herein with respect to Figure 1 may have similar cross-sectional structures and similarly incorporate the photocurable inks described herein. While the display 230 is flat in the embodiment illustrated in Figure 2, embodiments are also contemplated in which the display 230 is curved and the glass article 400 includes one or more curved surfaces (e.g., as a result of being cold-formed or hot-formed to have a suitable curved shape).

[0030] As shown in FIG. 2, the glass article 400 includes at least a substrate 450 and an opaque layer 500, optionally with a light management layer 460. The substrate 450 has a first side 470 facing the viewer and a second side 480 on which the opaque layer 500 is at least partially disposed. As used herein, the term "disposing" includes coating, depositing, and / or forming a material on a surface using any method known in the art. The disposed material may constitute a layer, as defined herein. As used herein, the phrase "disposed on" includes instances where a material is formed on a surface such that the material is in direct contact with the surface, and also includes instances where a material is formed on a surface with one or more intervening materials between the disposed material and the surface. The intervening materials may constitute a layer, as described herein. The term "layer" may include a single layer or may include one or more sublayers. Such sublayers may be in direct contact with each other. The sublayers may be formed from the same material or from two or more different materials. In one or more alternative embodiments, such sublayers may have intervening layers of different materials disposed therebetween. In one or more embodiments, a layer may include one or more adjacent continuous layers and / or one or more discontinuous interrupted layers (i.e., layers having different materials formed adjacent to one another). The layers or sublayers may be formed by any method known in the art, including separate deposition processes or sequential deposition processes. In one or more embodiments, the layers may be formed using only sequential deposition processes or only separate deposition processes.

[0031] In an embodiment, the substrate 450 is a glass substrate, optionally chemically strengthened, having a thickness of 0.05 to 2.0 mm. In one or more embodiments, the substrate 450 may be a transparent plastic, such as PMMA, polycarbonate, or a glass material (which may be strengthened, if desired). As described in more detail below, in an embodiment, an opaque layer 500 is printed on the second side 480 of the substrate 450. In an embodiment, the opaque layer 500 is printed on the light management layer 460, if included. Certain existing UV curable inks have been demonstrated to meet at least some of the requirements set forth herein with respect to Tables 1-4, but have been shown to be incompatible with the light management layer 460 (e.g., lacking the necessary adhesion). For example, existing photocurable inks, when used in the opaque layer, may chemically react (either during deposition or after environmental testing) with the inks of the light management layer 460, changing the characteristics (e.g., color, size) of those ink layers. Existing photocurable inks can also diffuse into and degrade the performance of light management layer 460. The photocurable inks described herein, when used to form opaque layer 500 and printed over light management layer 460, do not suffer from such defects, yet provide adequate adhesion to substrate 450 even in the presence of light management layer 460.

[0032] In an embodiment, the glass article 400 includes a functional surface layer 490. The functional surface layer 490 can be made to provide one or more of a variety of functions. For example, the functional surface layer 490 can be an optical coating made to provide easy-to-clean performance, anti-glare properties, anti-reflective properties, and / or a half-mirror coating. In the case of an anti-reflective functional surface layer, such a layer can be formed using multiple layers having alternating high and low refractive indices. Non-limiting examples of low refractive index films include SiO2, MgF2, and Al2O3, and non-limiting examples of high refractive index films include Nb2O5, TiO2, ZrO2, HfO2, and Y2O3. In an embodiment, the total thickness of such an optical coating (which may be disposed over the anti-glare surface or the smooth substrate surface) is 5 nm to 750 nm. In addition, in an embodiment, the functional surface layer 490 that provides easy-to-clean performance also provides coatings / treatments for enhanced feel and / or fingerprint reduction for touch panels. In some embodiments, the functional surface layer 490 is integral with the first side of the substrate. For example, such a functional surface layer may include an etched surface on the first side of the substrate 450 that provides an anti-glare surface (or a haze of, for example, 2% to 20%).

[0033] In embodiments, the opaque layer 500 is made from one or more of the photocurable inks described herein. Thus, the opaque layer 500 may have a relatively high optical density, for example, an optical density greater than 4, to block the transmission of light. In embodiments, the opaque layer 500 is used to block light from passing through certain areas of the glass article 400. In embodiments, the opaque layer 500 obscures functional or non-decorative elements provided for the operation of the glass article 400. In embodiments, the opaque layer 500 is provided to outline backlit icons and / or other graphics (not shown) to increase contrast at the edges of such icons and / or graphics. The opaque layer 500 can be any color; however, in certain embodiments, the opaque layer 500 is black or gray. In embodiments, the opaque layer 500 is applied by inkjet printing onto the light management layer 460 and / or onto the second surface 480 of the substrate 450. Typically, the thickness of the opaque layer 500 is 25 μm or less (eg, 1.0 μm or more and 25.0 μm or less, 5.0 μm or more and 25.0 μm or less, 5.0 μm or more and 20.0 μm or less, 5.0 μm or more and 10.0 μm or less).

[0034] In embodiments, the opaque layer 500 may be deposited directly onto the second side 480 of the substrate 450 using a suitable inkjet process. In embodiments, prior to deposition of the opaque layer 500, the second side 480 may be primed using a suitable primer (e.g., an acryloxysilane primer) to enhance adhesion of the opaque layer 500 to the substrate 450. Any suitable treatment may be used on the second side 480 to enhance adhesion of the opaque layer 500 to the substrate 450.

[0035] In an embodiment as shown in FIG. 2, the glass article 400 is placed over or in front of the display 540. In one or more embodiments, the display 540 may include a touch-enabled display including a display and a touch panel. Exemplary displays include LED displays, DLP MEMS chips, LCDs, OLEDs, transmissive displays, and the like. The glass article 400 may generally have an average transmittance from 380 nm to 750 nm of 10% or more (e.g., 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more). However, due to the high optical density of the opaque layer 500, the area of ​​the glass article 400 with the opaque layer 500 has a relatively low light transmittance (e.g., an average transmittance of 0.1% or less in the visible spectrum). Thus, the boundaries of the opaque layer 500 may define a display area 520 where the glass article 400 exhibits a relatively high light transmittance to facilitate visibility of the image generated by the display 540.

[0036] In the illustrated embodiment, the opaque layer 500 covers the edges 550 of the display 540 to obscure the edges 550 through the first side 470. The opaque layer 500 may also be used to obscure various other components (e.g., electrical connections, mechanical housings, etc.). The opaque layer 500 generally allows desired portions of the display 540 to be visible to a user viewing the first side 470.

[0037] Still referring to FIG. 2, the light management layer 460, if included, may be printed onto the substrate 450. In an embodiment, the light management layer 460 is formed from a suitable thermally or UV curable ink. The light management layer 460 may generally reduce the transmission of light through the glass article 400 such that the glass article 400 presents a similar appearance to a user whether the display 540 is powered on or off. For example, the light management layer 460 may obscure the edges of the viewing area 520, making the boundaries of the viewing area 520 less noticeable to a viewer when the display is powered off. The light management layer 460 may generally be configured as described in any of International Publication No. WO 2019 / 055458 A1, entitled "Black Deadfront for Display Device and Methods," International Publication No. WO 2020 / 205519 A1, entitled "Decorated Glass Having a Printed Ink Layer," or International Publication No. WO 2021 / 118835 A1, entitled "Display Devices and Articles with Color-Matched Display and Non-Display Areas," each of which is incorporated herein by reference in its entirety.

[0038] Figure 3 illustrates a flow diagram of a method 600 for forming a glass article having an opaque layer, in accordance with one or more embodiments of the present disclosure. Method 600 may be performed to manufacture glass article 400 as described herein with respect to Figure 2. Accordingly, reference is made to various components described with respect to Figure 2 to assist in describing the method. It should be understood that other glass articles may be formed by performance of method 600, and that method 600 is not limited to any particular number or order of process steps.

[0039] At block 602, substrate 450 is manufactured. Any suitable glass manufacturing process may be used, such as fusion downdraw, float, etc. Additional details regarding glass forming methods are provided herein. At block 604, substrate 450 is processed. For example, in an embodiment, substrate 450 is subjected to a strengthening treatment (e.g., ion exchange strengthening, heat strengthening). Additional details regarding strengthening treatments that may be applied to substrate 450 are provided herein.

[0040] In embodiments, the treatment applied to substrate 450 during block 604 may be used to form functional surface layer 490. For example, in embodiments, substrate 450 is chemically etched such that at least first surface 470 exhibits anti-glare properties. A suitable anti-reflective and / or ETC coating may also be deposited on first surface 470 by a suitable deposition process. In embodiments, second surface 480 may be primed (e.g., using a suitable chemical primer or ink) to promote adhesion of opaque layer 500 thereto. In embodiments, light management layer 460 may be deposited on second surface 480 and cured (e.g., a suitable ink may be cured thermally or by exposure to electromagnetic radiation).

[0041] In block 606, a photocurable ink is deposited on the second side 480 to begin the formation of the opaque layer 500. As described herein, a suitable inkjet printing device may be used to deposit droplets of suitable size on the second side 480 such that the photocurable ink forms a suitable pattern. The various parameters (e.g., control waveform, travel speed, deposition temperature) used to operate the inkjet printing device will vary depending on the composition of the photocurable ink and the desired deposition pattern. As noted with respect to block 604, the second side 480 may have an ink primer, such as those described herein, applied thereto prior to deposition of the photocurable ink. In block 608, the photocurable ink is cured on the second side 480 by exposure to electromagnetic radiation generated by an ultraviolet LED. In embodiments, the UV LEDs emit radiation having a relatively narrow bandwidth (e.g., 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less) surrounding a central UV wavelength (e.g., 375 nm, 380 nm, 385 nm, 390 nm, 395 nm, 400 nm). The operating parameters of the UV LEDs (e.g., output intensity, duration of exposure) will vary depending on various aspects of the opaque layer 500 (e.g., thickness, composition).

[0042] In embodiments, blocks 606 and 608 may be performed while substrate 450 has a planar shape. In embodiments, blocks 606 and 608 may be performed while substrate 450 is in a curved shape. For example, after performing at least some of the processes described with respect to block 604, substrate 450 may be cold formed by methods described herein, and opaque layer 500 may be formed on the cold formed glass substrate. In embodiments, a suitable display panel is laminated to the glass substrate such that opaque layer 500 at least partially covers the display panel. EXAMPLES

[0043] The embodiments of the present disclosure will be further understood in light of the following examples.

[0044] Examples 1 to 3 Photocurable inks having different compositions were formulated. An additional carbon black dispersant was used in the pigment dispersant of each of the inks. The concentration of the pigment was between 10% and 20% by weight of each of the photocurable inks. In Example 1, a pigment dispersant containing a carbon black pigment from Penn Color, Inc. with propoxylated neopentyl glycol diacrylate (PO-PPGDA) as a monomer was used. This carbon black pigment constituted 10% by weight of the photocurable ink. In Example 2, a pigment dispersant containing a carbon black pigment from Penn Color, Inc. with trimethylolpropane triacrylate (TMPTA) as a monomer was used. This carbon black pigment constituted 20% by weight of the photocurable ink. In Example 3, a pigment dispersant containing a carbon black pigment from Sun Chemical® with propoxylated neopentyl glycol diacrylate (PO-PPGDA) as a monomer was used. This carbon black pigment constituted 10% by weight of the photocurable ink. These inks were jetted onto chemically strengthened glass substrates using a research-grade printhead at deposition temperatures between 55° C. and 65° C. An opaque layer was formed on the glass using a Dimatix® inkjet cartridge designed to deposit 10 pL drop volumes at 1270 dpi resolution. The inks were then cured using an ultraviolet LED emitting radiation centered at 395 nm.

[0045] The samples made according to Examples 1-3 were measured for the optical density of the resulting opaque layer using a densitometer. Figure 4 shows a chart 700 of optical density as a function of opaque layer thickness for the various samples made. As shown by point 702, the opaque layer made from Example 2 (having the highest weight percent pigment) produced an optical density of greater than 4.0 at a thickness of less than 8 μm, demonstrating the effectiveness of the photocurable inks described herein. Each of the samples shown in Figure 4 was also tested for adhesion and passed the adhesion test (adhesion of 4B or greater as measured according to ASTM 3359) when the glass was primed with an acryloxysilane primer prior to printing.

[0046] Samples made using the ink formulation of Example 1 were subjected to high temperature and humidity testing by heating the samples to 85° C. in a 95% relative humidity environment for a period of 500 hours, and then tested for adhesion according to ASTM 3359. The results of the cross-hatch adhesion test are shown in FIG. 5. As can be seen, the appearance of the opaque layer 802 was not significantly affected by the adhesion test, and only a small portion of the opaque layer (shown on the underside of the tape 804 used in the test) was removed along the cut edge. Such results demonstrate the reliability and durability of the photocurable inks described herein.

[0047] Example 4 Another example was formulated using the composition shown in Table 6. As can be seen, the ink formulated according to Example 4 contained 10% by weight carbon black pigment. The ink was jetted onto chemically strengthened glass using a research grade printhead at 60° C., and the printed parts were cured using UV LEDs and measured for optical density and thickness. The optical density was measured to be 4.2 at a thickness of 21 μm. The ink passed the adhesion test (4B or better as measured according to ASTM 3359). It is believed that higher optical densities may be achieved at smaller thicknesses using pigment dispersants with more dilute monomers.

[0048] [Table 6]

[0049] Example 5 Another example was formulated using the composition shown in Table 7. This example differs from the previous example in that the photoinitiator package was modified to reduce the overall percentage in the formulation while maintaining cure, allowing for greater formulation flexibility. In an embodiment, the photoinitiator package is included in an amount of 5 wt% or less (e.g., 2 wt% or more and 4.5 wt% or less, 2.5 wt% or more and 4.0 wt% or less) to provide formulation flexibility (e.g., to facilitate the addition of viscosity modifiers). Sun Chemical D3310-FX-K (25% in IBOA) was observed to have a much lower viscosity than UVDJ207 (25% in PONPGDA), and was therefore more attractive for inkjet printing. A mixed design of experiments was also used to optimize the formulation for viscosity, printability, and overall thickness vs. OD. From this work, it was found that dipropylene glycol diacrylate (DPGDA M222) performed better than hydroxyl pivalate neopentyl glycol diacrylate (HPNDA M210), especially when combined with dipentaerythritol hexaacrylate (DPHA M600) and vinyl methyl oxazolidinone (Vmox). DPHA M600 added additional crosslinking to the ink and aided in curing. Vmox replaced n-vinyl caprolactam as a better viscosity modifier while aiding in adhesion. As shown in Table 7, the ink formulated according to Example 5 contained 11.25% by weight carbon black pigment. The ink was jetted on chemically strengthened glass using a production KM1024iSHE printhead at 50° C., and the printed parts were cured using UV LEDs and measured for optical density and thickness.

[0050] The printed parts were formed using a three-pulse waveform (including a first 10 microsecond pulse at 1V, a second 10 microsecond pulse at -1V, and a third 10 microsecond pulse at 0V) with a total duration of 30 microseconds. Drop volumes varied from 2.9 pL to 9.0 pL. Drop velocities varied from 2.67 m / s to 2.86 m / s. Drop angles varied from 0.21° to 0.60°. FIG. 7 shows a plot of optical density as a function of thickness for several samples produced according to Example 5. As can be seen, the formulation provided an optical density of greater than 4.0 for thicknesses greater than 10 μm. For example, the optical density was measured to be 4.8 at a thickness of 11 μm. Example 5 was subjected to high temperature and humidity testing by heating the sample to 85° C. in a 95% relative humidity environment for a period of 500 hours, and then tested for adhesion according to ASTM 3359. As shown in FIG. 8, the ink passed the adhesion test (4B or better as measured according to ASTM 3359). The appearance of the opaque layer 1000 was not significantly affected by the adhesion test, with only a small portion of the opaque layer (shown on the underside of the tape 1002 used in the test) being removed along the cut edge. Such results demonstrate the reliability and durability of the photocurable inks described herein.

[0051] [Table 7]

[0052] counterexample Two commercially available UV-curable inks (Inks A and B) were deposited on pre-primed, chemically strengthened glass and tested under high temperature and humidity test conditions (85° C. and 95% relative humidity for 500 hours). Figures 6A and 6B show the samples after testing. As can be seen, both samples showed visible cracks 902, 904 as a result of shrinkage of the opaque layer. The photocurable ink showed no such visible cracks when exposed to high temperature conditions for extended periods of time, demonstrating the improved durability and reliability of the inks described herein.

[0053] Glass Material The various glass layers of the decorative glasses described herein, such as substrate 450, may be formed from any suitable glass composition, including soda-lime glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, alkali-containing aluminosilicate glass, alkali-containing borosilicate glass, and alkali-containing aluminoborosilicate glass.

[0054] Unless otherwise stated, the glass compositions disclosed herein are listed in mole percent (mol %) as analyzed on an oxide basis.

[0055] In one or more embodiments, the glass composition may include SiO2 in an amount in the range from about 66 mol% to about 80 mol%, about 67 mol% to about 80 mol%, about 68 mol% to about 80 mol%, about 69 mol% to about 80 mol%, about 70 mol% to about 80 mol%, about 72 mol% to about 80 mol%, about 65 mol% to about 78 mol%, about 65 mol% to about 76 mol%, about 65 mol% to about 75 mol%, about 65 mol% to about 74 mol%, about 65 mol% to about 72 mol%, or about 65 mol% to about 70 mol%, and all ranges and sub-ranges therebetween.

[0056] In one or more embodiments, the glass composition includes Al2O3 in an amount greater than about 4 mol%, or greater than about 5 mol%. In one or more embodiments, the glass composition includes Al2O3 in a range from greater than about 7 mol% to about 15 mol%, from greater than about 7 mol% to about 14 mol%, from about 7 mol% to about 13 mol%, from about 4 mol% to about 12 mol%, from about 7 mol% to about 11 mol%, from about 8 mol% to about 15 mol%, from about 9 mol% to about 15 mol%, from about 9 mol% to about 15 mol%, from about 10 mol% to about 15 mol%, from about 11 mol% to about 15 mol%, or from about 12 mol% to about 15 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the upper limit of Al2O3 may be about 14 mol%, 14.2 mol%, 14.4 mol%, 14.6 mol%, or 14.8 mol%.

[0057] In one or more embodiments, the glass layer herein is described as being made as an aluminosilicate glass article or from an aluminosilicate glass composition. In such embodiments, the glass composition or article formed therefrom includes SiO2 and Al2O3 and is not a soda-lime silicate glass. In that regard, the glass composition or article formed therefrom includes Al2O3 in an amount of about 2 mol% or more, 2.25 mol% or more, 2.5 mol% or more, about 2.75 mol% or more, or about 3 mol% or more.

[0058] In one or more embodiments, the glass composition includes B2O3 (e.g., about 0.01 mol% or more). In one or more embodiments, the glass composition includes B2O3 in an amount ranging from about 0 mol% to about 5 mol%, from about 0 mol% to about 4 mol%, from about 0 mol% to about 3 mol%, from about 0 mol% to about 2 mol%, from about 0 mol% to about 1 mol%, from about 0 mol% to about 0.5 mol%, from about 0.1 mol% to about 5 mol%, from about 0.1 mol% to about 4 mol%, from about 0.1 mol% to about 3 mol%, from about 0.1 mol% to about 2 mol%, from about 0.1 mol% to about 1 mol%, from about 0.1 mol% to about 0.5 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the glass composition is substantially free of B2O3.

[0059] As used herein, the phrase "substantially free" with respect to a component of a composition means that the component is not actively or intentionally added to the composition during initial batch formulation, but may be present as an impurity in an amount less than about 0.001 mole percent.

[0060] In one or more embodiments, the glass composition optionally includes P2O5 (e.g., about 0.01 mol% or more). In one or more embodiments, the glass composition includes P2O5 in a non-zero amount up to 2 mol%, up to 1.5 mol%, up to 1 mol%, or up to 0.5 mol%. In one or more embodiments, the glass composition is substantially free of P2O5.

[0061] In one or more embodiments, the glass composition may include R2O (the sum of alkali metal oxides, such as Li2O, Na2O, KO, Rb2O, and Cs2O) in a total amount of about 8 mol% or more, about 10 mol% or more, or about 12 mol% or more. In some embodiments, the glass composition includes R2O in a total amount in the range from about 8 mol% to about 20 mol%, about 8 mol% to about 18 mol%, about 8 mol% to about 16 mol%, about 8 mol% to about 14 mol%, about 8 mol% to about 12 mol%, about 9 mol% to about 20 mol%, about 10 mol% to about 20 mol%, about 11 mol% to about 20 mol%, about 12 mol% to about 20 mol%, about 13 mol% to about 20 mol%, about 10 mol% to about 14 mol%, or 11 mol% to about 13 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the glass composition may be substantially free of Rb2O, Cs2O, or both Rb2O and Cs2O. In one or more embodiments, R2O may include only the total amounts of Li2O, Na2O, and K2O. In one or more embodiments, the glass composition may include at least one alkali metal oxide selected from Li2O, Na2O, and K2O, where the alkali metal oxide is present in an amount of about 8 mol % or greater.

[0062] In one or more embodiments, the glass composition includes Na2O in an amount of about 8 mol% or more, about 10 mol% or more, or about 12 mol% or more. In one or more embodiments, the glass composition includes Na2O in an amount of about 8 mol% to about 20 mol%, about 8 mol% to about 18 mol%, about 8 mol% to about 16 mol%, about 8 mol% to about 14 mol%, about 8 mol% to about 12 mol%, about 9 mol% to about 20 mol%, about 10 mol% to about 20 mol%, about 11 mol% to about 20 mol%, about 12 mol% to about 20 mol%, about 13 mol% to about 20 mol%, about 10 mol% to about 14 mol%, or 11 mol% to about 13 mol%, and all ranges and sub-ranges therebetween.

[0063] In one or more embodiments, the glass composition includes less than about 4 mol% K2O, less than about 3 mol% K2O, or less than about 1 mol% K2O. In some cases, the glass composition may include KO in an amount in the range from about 0 mol% to about 4 mol%, from about 0 mol% to about 3.5 mol%, from about 0 mol% to about 3 mol%, from about 0 mol% to about 2.5 mol%, from about 0 mol% to about 2 mol%, from about 0 mol% to about 1.5 mol%, from about 0 mol% to about 1 mol%, from about 0 mol% to about 0.5 mol%, from about 0 mol% to about 0.2 mol%, from about 0 mol% to about 0.1 mol%, from about 0.5 mol% to about 4 mol%, from about 0.5 mol% to about 3.5 mol%, from about 0.5 mol% to about 3 mol%, from about 0.5 mol% to about 2.5 mol%, from about 0.5 mol% to about 2 mol%, from about 0.5 mol% to about 1.5 mol%, or from about 0.5 mol% to about 1 mol%, and all ranges and sub-ranges therebetween. In one or more embodiments, the glass composition is substantially free of K2O.

[0064] In one or more embodiments, the glass composition is substantially free of Li2O.

[0065] In one or more embodiments, the amount of Na2O in the composition may be greater than the amount of Li2O. In some cases, the amount of Na2O may be greater than the combined amount of Li2O and K2O. In one or more alternative embodiments, the amount of Li2O in the composition may be greater than the amount of Na2O or the combined amount of Na2O and K2O.

[0066] In one or more embodiments, the glass composition may include RO (which is the sum of alkaline earth metal oxides, such as CaO, MgO, BaO, ZnO, and SrO) in a total amount ranging from about 0 mol% to about 2 mol%. In some embodiments, the glass composition includes RO in a non-zero amount up to about 2 mol%. In one or more embodiments, the glass composition includes RO in an amount from about 0 mol% to about 1.8 mol%, from about 0 mol% to about 1.6 mol%, from about 0 mol% to about 1.5 mol%, from about 0 mol% to about 1.4 mol%, from about 0 mol% to about 1.2 mol%, from about 0 mol% to about 1 mol%, from about 0 mol% to about 0.8 mol%, from about 0 mol% to about 0.5 mol%, and all ranges and sub-ranges therebetween.

[0067] In one or more embodiments, the glass composition includes CaO in an amount less than about 1 mol%, less than about 0.8 mol%, or less than about 0.5 mol%. In one or more embodiments, the glass composition is substantially free of CaO. In some embodiments, the glass composition includes MgO in an amount from about 0 mol% to about 7 mol%, from about 0 mol% to about 6 mol%, from about 0 mol% to about 5 mol%, from about 0 mol% to about 4 mol%, from about 0.1 mol% to about 7 mol%, from about 0.1 mol% to about 6 mol%, from about 0.1 mol% to about 5 mol%, from about 0.1 mol% to about 4 mol%, from about 1 mol% to about 7 mol%, from about 2 mol% to about 6 mol%, or from about 3 mol% to about 6 mol%, and all ranges and sub-ranges therebetween.

[0068] In one or more embodiments, the glass composition includes ZrO2 in an amount of about 0.2 mol% or less, about 0.18 mol% or less, about 0.16 mol% or less, about 0.15 mol% or less, about 0.14 mol% or less, about 0.12 mol% or less, In one or more embodiments, the glass composition includes ZrO2 in an amount of about 0.01 mol% to about 0.2 mol%, about 0.01 mol% to about 0.18 mol%, about 0.01 mol% to about 0.16 mol%, about 0.01 mol% to about 0.15 mol%, about 0.01 mol% to about 0.14 mol%, about 0.01 mol% to about 0.12 mol%, or about 0.01 mol% to about 0.10 mol%, and all ranges and sub-ranges therebetween.

[0069] In one or more embodiments, the glass composition includes SnO2 in an amount of about 0.2 mol% or less, about 0.18 mol% or less, about 0.16 mol% or less, about 0.15 mol% or less, about 0.14 mol% or less, about 0.12 mol% or less, In one or more embodiments, the glass composition includes SnO2 in an amount of about 0.01 mol% to about 0.2 mol%, about 0.01 mol% to about 0.18 mol%, about 0.01 mol% to about 0.16 mol%, about 0.01 mol% to about 0.15 mol%, about 0.01 mol% to about 0.14 mol%, about 0.01 mol% to about 0.12 mol%, or about 0.01 mol% to about 0.10 mol%, and all ranges and sub-ranges therebetween.

[0070] In one or more embodiments, the glass composition may include oxides that impart color or tint to the glass article. In some embodiments, the glass composition includes oxides that prevent discoloration of the glass article when exposed to ultraviolet light. Examples of such oxides include, without limitation, oxides of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Ce, W, and Mo.

[0071] In one or more embodiments, the glass composition includes Fe, expressed as Fe2O3, where Fe is present in an amount up to (including) about 1 mol%. In some embodiments, the glass composition is substantially free of Fe. In one or more embodiments, the glass composition includes Fe2O3 in an amount of about 0.2 mol% or less, about 0.18 mol% or less, about 0.16 mol% or less, about 0.15 mol% or less, about 0.14 mol% or less, or about 0.12 mol% or less. In one or more embodiments, the glass composition includes Fe2O3 in the range from about 0.01 mol% to about 0.2 mol%, from about 0.01 mol% to about 0.18 mol%, from about 0.01 mol% to about 0.16 mol%, from about 0.01 mol% to about 0.15 mol%, from about 0.01 mol% to about 0.14 mol%, from about 0.01 mol% to about 0.12 mol%, or from about 0.01 mol% to about 0.10 mol%, and all ranges and sub-ranges therebetween.

[0072] When the glass composition includes TiO2, TiO2 may be present in an amount of about 5 mol% or less, about 2.5 mol% or less, about 2 mol% or less, or about 1 mol% or less. In one or more embodiments, the glass composition may be substantially free of TiO2.

[0073] Exemplary glass compositions include SiO2 in an amount ranging from about 65 mol% to about 75 mol%, Al2O3 in an amount ranging from about 8 mol% to about 14 mol%, Na2O in an amount ranging from about 12 mol% to about 17 mol%, K2O in an amount ranging from about 0 mol% to about 0.2 mol%, and MgO in an amount ranging from about 1.5 mol% to about 6 mol%. Optionally, SnO2 may be included in amounts as otherwise disclosed herein.

[0074] Properties of tempered glass In one or more embodiments, the cold-formed glass sheet 2010 or other glass layers of any of the decorative glass embodiments described herein may be formed from a tempered glass sheet or article. In one or more embodiments, the glass articles used to form the layers of the decorative glass structures described herein may be tempered to have compressive stresses that extend from the surface to a depth of compression (DOC). The compressive stress areas are balanced with a central portion that exhibits tensile stress. At the DOC, the stresses cross over from positive (compressive) to negative (tensile).

[0075] In one or more embodiments, the glass articles used to form the layers of the decorative glass structures described herein may be mechanically strengthened by exploiting the mismatch in thermal expansion coefficients between portions of the glass to create areas of compressive stress and a central region exhibiting tensile stress. In some embodiments, the glass articles may be thermally strengthened by heating the glass above its glass transition temperature and then quenching.

[0076] In one or more embodiments, the glass articles used to form the layers of the decorative glass structures described herein may be chemically strengthened by ion exchange. In the ion exchange process, ions at or near the surface of the glass article are replaced - i.e., exchanged - with larger ions having the same valence or oxidation state. In embodiments where the glass article is made from an alkali aluminosilicate glass, the ions in the surface layer of the article and the larger ions are Li + , Na + , K + , Rb + , and Cs + Alternatively, the monovalent cations in the surface layer are Ag + In such embodiments, the exchanged monovalent ions (or cations) create stress in the glass article.

[0077] The ion exchange process is typically carried out by immersing the glass article in a molten salt bath (or two or more molten salt baths) containing the larger ions to be exchanged for the smaller ions in the glass article. It should be noted that aqueous salt baths may also be utilized. In addition, the composition of the bath may contain more than one type of larger ion (e.g., Na + and K. + ) or one larger ion. It will be recognized by those skilled in the art that the parameters of the ion exchange process, including but not limited to the bath composition and temperature, immersion time, number of immersions of the glass article in the salt bath, use of multiple salt baths, additional steps such as slow cooling, washing, etc., will generally depend on the composition of the glass layer of the decorative glass structure (including the structure of the article and any crystalline phases present) and the desired DOC and CS of the glass layer of the decorative glass structure resulting from the tempering.

[0078] Exemplary molten bath compositions may include nitrates, sulfates, and chlorides of larger alkali metal ions. Typical nitrates include KNO3, NaNO3, LiNO3, NaSO4, and combinations thereof. The temperature of the molten salt bath generally ranges from about 380°C to about 450°C, while the immersion time ranges from about 15 minutes to about 100 hours, depending on the thickness of the glass, the temperature of the bath, and the diffusivity of the glass (or monovalent ions). However, temperatures and immersion times different from those described above may also be used.

[0079] According to one or more embodiments, the glass article used to form the layer of decorative glass may be immersed in a molten salt bath of 100% NaNO3, 100% KNO3, or a combination of NaNO3 and KNO3 having a temperature of about 370° C. to about 480° C. In some embodiments, the glass layer of the decorative glass may be immersed in a molten mixed salt bath including about 5% to about 90% KNO3 and about 10% to about 95% NaNO3. In some embodiments, the glass article may be immersed in a first bath and then in a second bath. The first and second baths may have different compositions and / or temperatures. The immersion times in the first and second baths may vary. For example, the immersion in the first bath may be longer than the immersion in the second bath.

[0080] According to one or more embodiments, the glass article used to form the layers of the decorative glass structure may be immersed in a molten mixed salt bath comprising NaNO3 and KNO3 (e.g., 49% / 51%, 50% / 50%, 51% / 49%) having a temperature of less than about 420°C (e.g., about 400°C or about 380°C) for less than about 5 hours, or even less than about 4 hours.

[0081] The ion exchange conditions can be adjusted to increase the gradient, or to provide a "spike" in the stress profile at or near the surface of the resulting glass layer of the decorative glass structure. The spike will result in a larger surface CS value. The spike can be achieved with one bath or multiple baths, which have one composition or a mixture of compositions due to the specific nature of the glass compositions used in the glass layers of the decorative glass structures described herein.

[0082] In one or more embodiments in which multiple monovalent ions are exchanged into a glass article used to form a layer of a decorative glass structure, different monovalent ions may be exchanged to different depths within the glass layer (producing different amounts of stress within the glass article at different depths), and the resulting relative depths of the stress-producing ions can be determined, thereby producing different characteristics of the stress profile.

[0083] CS is measured using means known in the art, such as by a surface stress meter (FSM) using commercially available equipment, such as the FSM-6000 manufactured by Orihara Seisakusho Co., Ltd. (Japan). Surface stress measurements rely on precise measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is then measured by methods known in the art, such as the fiber method and the four-point bending method, both of which are described in ASTM standard C770-98 (2013), entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," and the bulk cylinder method, the contents of which are incorporated herein in their entirety by reference. As used herein, CS may be the "maximum compressive stress," which is the highest compressive stress value measured within the compressive stress layer. In some embodiments, the maximum compressive stress is located at the surface of the glass article. In other embodiments, the maximum compressive stress may occur at some depth below the surface, giving the compressive profile the appearance of a "buried peak."

[0084] DOC can be measured by FSM or by a Scattered Light Polariscope (SCALP) (such as the SCALP-04 Scattered Light Polariscope available from GlasStress Ltd., Tallinn, Estonia). If the glass article is chemically strengthened by an ion exchange process, then either FSM or SCALP can be used depending on which ions are exchanged into the glass article. If the stress in the glass article is caused by exchanging potassium ions into the glass article, then FSM is used to measure the DOC. If the stress in the glass article is caused by exchanging sodium ions into the glass article, then SCALP is used to measure the DOC. If the stress in the glass article is caused by exchanging both potassium and sodium ions into the glass article, then DOC is measured by SCALP. Because the exchange depth of the sodium ions is considered to represent the DOC, and the exchange depth of the potassium ions is considered to represent the change in the magnitude of the compressive stress (and not the change in the stress from compressive to tensile); the exchange depth of the potassium ions in such glass articles is measured by FSM. Central tension or CT is the maximum tensile stress and is measured by SCALP.

[0085] In one or more embodiments, the glass articles used to form the layers of the decorative glass structure may be strengthened to exhibit a DOC, expressed as a percentage of the thickness t (as described herein) of the glass article. For example, in one or more embodiments, the DOC may be about 0.05t or more, about 0.1t or more, about 0.11t or more, about 0.12t or more, about 0.13t or more, about 0.14t or more, about 0.15t or more, about 0.16t or more, about 0.17t or more, about 0.18t or more, about 0.19t or more, about 0.2t or more, or about 0.21t or more. In some embodiments, the DOC may be in the range of about 0.08t to 0.25t, about 0.09t to 0.25t, about 0.18t to 0.25t, about 0.11t to 0.25t, about 0.12t to 0.25t, about 0.13t to 0.25t, about 0.14t to 0.25t, about 0.15t to 0.25t, about 0.08t to 0.24t, about 0.08t to 0.23t, about 0.08t to 0.22t, about 0.08t to 0.21t, about 0.08t to 0.2t, about 0.08t to 0.19t, about 0.08t to 0.18t, about 0.08t to 0.17t, about 0.08t to 0.16t, or about 0.08t to 0.15t. In some cases, the DOC may be about 20 μm or less. In one or more embodiments, the DOC may be about 40 μm or more (e.g., about 40 μm to about 300 μm, about 50 μm to about 300 μm, about 60 μm to about 300 μm, about 70 μm to about 300 μm, about 80 μm to about 300 μm, about 90 μm to about 300 μm, about 100 μm to about 300 μm, about 110 μm to about 300 μm, about 120 μm to about 300 μm, about 140 μm to about 300 μm, about 150 μm to about 300 μm, about 40 μm to about 290 μm, about 40 μm to about 280 μm, about 40 μm to about 260 μm, about 40 μm to about 250 μm, about 40 μm to about 240 μm, about 40 μm to about 230 μm, about 40 μm to about 220 μm, about 40 μm to about 210 μm, about 40 μm to about 200 μm, about 40 μm to about 180 μm, about 40 μm to about 160 μm, about 40 μm to about 150 μm, about 40 μm to about 140 μm, about 40 μm to about 130 μm, about 40 μm to about 120 μm, about 40 μm to about 110 μm, or about 40 μm to about 100 μm).

[0086] In one or more embodiments, the glass articles used to form the layers of the decorative glass structure may have a CS (which may be found at the surface or at a depth within the glass article) of about 200 MPa or more, 300 MPa or more, 400 MPa or more, about 500 MPa or more, about 600 MPa or more, about 700 MPa or more, about 800 MPa or more, about 900 MPa or more, about 930 MPa or more, about 1000 MPa or more, or about 1050 MPa or more.

[0087] In one or more embodiments, the glass articles used to form the layers of the decorative glass structure may have a maximum tensile stress or central tension (CT) of about 20 MPa or more, about 30 MPa or more, about 40 MPa or more, about 45 MPa or more, about 50 MPa or more, about 60 MPa or more, about 70 MPa or more, about 75 MPa or more, about 80 MPa or more, or about 85 MPa or more. In some embodiments, the maximum tensile stress or central tension (CT) may be in the range of about 40 MPa to about 100 MPa.

[0088] The embodiments of the present disclosure will be further understood in light of the following aspects.

[0089] Aspect (1) relates to a glass article comprising: a glass substrate having a first major surface and a second major surface opposite the first major surface; and an opaque layer disposed on the second major surface, the opaque layer made from a photocurable ink including at least 10% by weight pigment, the opaque layer having a thickness of 25 μm or less and an optical density of 4.0 or greater, the opaque layer, after being cured by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED"), exhibiting a pencil hardness of 3H or greater, as measured in accordance with ASTM 3363, and adhesion to the glass substrate of 4B or greater, as measured in accordance with ASTM 3359, after being exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0090] Aspect (2) of the present disclosure relates to a glass article according to aspect (1), wherein the photocurable ink comprises at least 30% by weight of a pigment dispersant, the pigment dispersant comprising 25% or more by weight of pigment and reactive monomer.

[0091] Aspect (3) of the present disclosure relates to a glass article according to aspect (2), wherein the pigment dispersant comprises 40% or more pigment by weight.

[0092] An embodiment (4) of the present disclosure relates to a glass article according to any one of embodiments (1) to (3), having a thickness of 10 μm or less.

[0093] An aspect (5) of the present disclosure relates to a glass article according to any one of aspects (1) to (4), wherein the photocurable ink does not contain halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.

[0094] An embodiment (6) of the present disclosure relates to the glass article according to any one of embodiments (1) to (5), wherein the pigment has an average particle size of 200 nm or less.

[0095] In the seventh aspect of the present disclosure, the opaque layer has a resistivity of 36 dyne / cm (10 -3 The glass article according to any of aspects (1) to (6) exhibits a post-cure surface tension of more than (N / m).

[0096] In an embodiment (8) of the present disclosure, the opaque layer has a thermal conductivity of 1×10 9 The present invention relates to a glass article according to any one of aspects (1) to (7) that exhibits an electrical resistivity of Ω / □ or more.

[0097] The embodiment (9) of the present disclosure is a glass article having a CIELAB SCI L of 30 or less when illuminated at an angle of 10° by a D65 light source. * The present invention relates to a glass article according to any one of aspects (1) to (8), which exhibits a value.

[0098] An embodiment (10) of the present disclosure is a glass article having a CIELAB SCI a value of -0.05 or more and 0.15 or less when illuminated at an angle of 10° by a D65 light source. * value, and CIELAB SCI b ≥ -0.3 and ≤ -0.1 * The present invention relates to a glass article according to any one of aspects (1) to (9), which exhibits a value.

[0099] An embodiment (11) of the present disclosure relates to a glass article according to any of embodiments (1)-(10), further including a light management layer disposed on the second major surface between the glass substrate and the opaque layer, the light management layer being formed from an ink and having an average light transmittance of 70% or less from 380 nm to 750 nm.

[0100] An aspect (12) of the present disclosure relates to a glass article according to any of aspects (1) to (11), wherein the glass substrate is made from at least one of soda-lime glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, alkali-containing aluminosilicate glass, or alkali-containing borosilicate glass.

[0101] An aspect (13) of the present disclosure relates to a display for a vehicle interior system, comprising: a glass substrate having a first major surface and a second major surface opposite the first major surface; an opaque layer disposed on the second major surface, the opaque layer made from a photocurable ink including at least 10% by weight of a pigment; and a display panel disposed on the second major surface, the opaque layer being disposed in a peripheral region of the second major surface and spanning an edge of the display panel, the opaque layer having a thickness of 25 μm or less and an optical density of 4.0 or greater, and the opaque layer, after curing by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED"), exhibits a pencil hardness of 3H or greater, as measured according to ASTM 3363, and adhesion to the glass substrate of 4B or greater, as measured according to ASTM 3359, when exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0102] An embodiment (14) of the present disclosure relates to a display according to embodiment (14), wherein the photocurable ink comprises at least 30% by weight of a pigment dispersant, and the pigment dispersant comprises 25% by weight or more of a pigment and a reactive monomer.

[0103] An embodiment (15) of the present disclosure relates to the display according to any one of embodiments (13) to (14), having a thickness of 10 μm or less.

[0104] An embodiment (16) of the present disclosure relates to a display according to any one of embodiments (13) to (15), wherein the photocurable ink does not contain halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.

[0105] An embodiment (17) of the present disclosure relates to a display according to any one of (13) to (16), in which the pigment has an average particle size of 200 nm or less.

[0106] An embodiment (18) of the present disclosure provides a display having a CIELAB SCI L of 30 or less when illuminated at an angle of 10° by a D65 light source. * The display according to any one of aspects (13) to (17) displays a value.

[0107] An embodiment (19) of the present disclosure is a display having a CIELAB SCI a value of greater than or equal to -0.05 and less than or equal to 0.15 when illuminated at an angle of 10° by a D65 light source. * value, and CIELAB SCI b ≥ -0.3 and ≤ -0.1 * The display according to any one of aspects (13) to (18) displays a value.

[0108] An embodiment (20) of the present disclosure relates to a display according to any of embodiments (13)-(19), further including a light management layer disposed on the second major surface between the glass substrate and the opaque layer, the light management layer being formed from an ink and having an average light transmittance of 70% or less from 380 nm to 750 nm.

[0109] Aspect (21) relates to a method of manufacturing a glass article, comprising: depositing a photocurable ink on a major surface of a glass substrate using an inkjet printhead at a deposition temperature of 65° C. or less, wherein during deposition, the photocurable ink has a viscosity of less than 25 cP, and the photocurable ink comprises at least 10% by weight of a pigment and at least 50% by weight of a reactive monomer; and curing the photocurable ink on the major surface by exposing the photocurable ink to an ultraviolet ("UV") light emitting diode ("LED") generated curing light to form an opaque layer, wherein the curing light has a bandwidth of 30 nm or less, wherein the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater, and wherein the opaque layer exhibits a pencil hardness of 3H or greater, as measured according to ASTM 3363, and adhesion to the glass substrate of 4B or greater, as measured according to ASTM 3359, when exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0110]

[0033] Embodiment (22) relates to the method according to embodiment (21), further comprising priming the major surface of the glass substrate with an acryloxysilane primer prior to depositing the photocurable ink.

[0111]

[0033] Aspect (23) relates to the method according to any of aspects (21)-(22), wherein the opaque layer covers a peripheral portion of the major surface such that the glass article exhibits a higher light transmittance from 380 nm to 750 nm in a central region not including the opaque layer.

[0112] Aspect (24) relates to the method according to any one of aspects (21) to (23), wherein the photocurable ink does not contain halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.

[0113] Embodiment (25) relates to the method according to any of embodiments (21) to (24), further comprising performing one or more additional surface treatments on the additional major surface of the glass substrate, the one or more additional surface treatments comprising at least one of chemically etching the additional major surface such that the additional major surface exhibits antiglare properties and depositing an antireflective coating on the additional major surface.

[0114]

[0031] Aspect (26) relates to the method according to any of Aspects (21)-(25), further comprising the step of depositing a light management layer on the major surface prior to depositing the light curable ink, the light management layer being made from an ink having a different composition than the light curable ink and at least partially overlapping the opaque layer.

[0115] Unless otherwise expressly stated, it is in no way intended that any method described herein be construed as requiring that its steps be performed in a particular order. Thus, unless a method claim actually recites the order in which its steps should be followed, or unless the claim or description is otherwise specifically stated to be limited to a particular order, no particular order is in any way intended to be implied. In addition, as used herein, nouns are intended to include one or more components or elements, and are not intended to be construed as meaning just one.

[0116] It will be apparent to those skilled in the art that various modifications and changes can be made without departing from the spirit or scope of the disclosed embodiments. Since modifications, combinations, subcombinations and modifications of the disclosed embodiments incorporating the spirit and substance of the embodiments will occur to those skilled in the art, the disclosed embodiments should be construed as including all within the scope of the appended claims and equivalents thereof.

[0117] Preferred embodiments of the present invention will be described below in detail.

[0118] EMBODIMENT 1 a glass substrate having a first major surface and a second major surface opposite the first major surface; and an opaque layer disposed on the second major surface, the opaque layer being made from a photocurable ink having at least 10% by weight pigment; the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater; The opaque layer is cured by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED") and then A pencil hardness of 3H or greater when measured in accordance with ASTM 3363; and Adhesion to glass substrates of 4B or greater when measured in accordance with ASTM 3359 after exposure to a temperature of 85°C at 95% relative humidity for a period of at least 500 hours; Indicating an opaque layer, A glass article comprising:

[0119] EMBODIMENT 2 2. The glass article of embodiment 1, wherein the photocurable ink comprises at least 30% by weight of a pigment dispersant, the pigment dispersant comprising 25% or more by weight of the pigment and reactive monomer.

[0120] EMBODIMENT 3 3. The glass article of embodiment 2, wherein the pigment dispersant comprises 40% or more by weight of the pigment.

[0121] EMBODIMENT 4 4. A glass article according to any one of claims 1 to 3, wherein the thickness is 10 μm or less.

[0122] EMBODIMENT 5 5. A glass article according to any one of claims 1 to 4, wherein the photocurable ink is free of halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.

[0123] EMBODIMENT 6 6. The glass article of any one of claims 1 to 5, wherein the pigment has an average particle size of 200 nm or less.

[0124] EMBODIMENT 7 The opaque layer has a resistivity of 36 dyne / cm(10 -3 7. The glass article of any one of claims 1 to 6, exhibiting a post-cure surface tension of greater than 1.0 N / m.

[0125] EMBODIMENT 8 The opaque layer has a thermal conductivity of 1×10 when measured according to ASTM D-257 at 100 V DC. 9 8. A glass article according to any one of claims 1 to 7, exhibiting an electrical resistivity of Ω / □ or more.

[0126] EMBODIMENT 9 When the glass article is illuminated at an angle of 10° by a D65 light source, it has a CIELAB SCI L of 30 or less. * 9. A glass article according to any one of claims 1 to 8, exhibiting a value.

[0127] EMBODIMENT 10 When the glass article is illuminated at an angle of 10° by a D65 light source, the CIELAB SCI a is greater than or equal to -0.05 and less than or equal to 0.15. * value, and CIELAB SCI b ≥ -0.3 and ≤ -0.1 * 10. A glass article according to any one of claims 1 to 9, exhibiting a value.

[0128] EMBODIMENT 11 11. The glass article of any one of claims 1 to 10, further comprising a light management layer disposed on the second major surface between the glass substrate and the opaque layer, the light management layer being formed from an ink and having an average light transmission of 70% or less from 380 nm to 750 nm.

[0129] EMBODIMENT 12 12. The glass article of any one of claims 1 to 11, wherein the glass substrate is made from at least one of soda-lime glass, aluminosilicate glass, borosilicate glass, aluminoborosilicate glass, alkali-containing aluminosilicate glass, or alkali-containing borosilicate glass.

[0130] EMBODIMENT 13 In displays for vehicle interior systems, a glass substrate having a first main surface and a second main surface opposite the first main surface; an opaque layer disposed on the second major surface, the opaque layer being made from a photocurable ink containing at least 10% by weight pigment; and a display panel disposed on the second major surface; Equipped with the opaque layer is disposed on a peripheral region of the second major surface, spanning an edge of the display panel; the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater; The opaque layer, after curing by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED"), A pencil hardness of 3H or greater when measured in accordance with ASTM 3363, and Adhesion to glass substrates of 4B or greater when measured in accordance with ASTM 3359 when exposed to a temperature of 85°C at 95% relative humidity for a period of at least 500 hours; A display for the in-vehicle system.

[0131] EMBODIMENT 14 14. The display of embodiment 13, wherein the photocurable ink comprises at least 30% by weight of a pigment dispersant, the pigment dispersant comprising 25% or more by weight of the pigment and reactive monomer.

[0132] EMBODIMENT 15 15. A display according to embodiment 13 or 14, wherein the thickness is 10 μm or less.

[0133] EMBODIMENT 16 16. The display of any one of embodiments 13 to 15, wherein the photocurable ink is free of halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.

[0134] EMBODIMENT 17 17. The display of any one of embodiments 13 to 16, wherein the pigment has an average particle size of 200 nm or less.

[0135] EMBODIMENT 18 A CIELAB SCI L of 30 or less when the display is illuminated at a 10° angle by a D65 light source * 18. A display according to any one of embodiments 13 to 17, which displays a value.

[0136] EMBODIMENT 19 A CIELAB SCI a value greater than or equal to -0.05 and less than or equal to 0.15 when the display is illuminated at an angle of 10° by a D65 light source. * value, and CIELAB SCI b ≥ -0.3 and ≤ -0.1 * 19. A display according to any one of embodiments 13 to 18, which displays a value.

[0137] EMBODIMENT 20 20. The display of any one of claims 13 to 19, further comprising a light management layer disposed on the second major surface between the glass substrate and the opaque layer, the light management layer being formed from an ink and having an average light transmittance of 70% or less from 380 nm to 750 nm.

[0138] EMBODIMENT 21 1. A method of making a glass article, comprising: depositing a photocurable ink onto a major surface of a glass substrate using an inkjet printhead at a deposition temperature of 65° C. or less, wherein during deposition, the photocurable ink has a viscosity of less than 25 cP, and the photocurable ink comprises at least 10% by weight of a pigment and at least 50% by weight of a reactive monomer; curing the photocurable ink on the major surface to form an opaque layer by exposing the photocurable ink to curing light generated by an ultraviolet ("UV") light emitting diode ("LED"), the curing light having a bandwidth of 30 nm or less; and the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater; The opaque layer is A pencil hardness of 3H or greater when measured in accordance with ASTM 3363, and A method which exhibits adhesion to a glass substrate of 4B or greater when measured in accordance with ASTM 3359 when exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

[0139] EMBODIMENT 22 22. The method of embodiment 21, further comprising priming a major surface of the glass substrate with an acryloxysilane primer prior to depositing the photocurable ink.

[0140] EMBODIMENT 23 23. The method of claim 21 or 22, wherein the opaque layer covers a peripheral portion of the major surface such that the glass article exhibits a higher light transmission from 380 nm to 750 nm in a central region not including the opaque layer.

[0141] EMBODIMENT 24 24. The method of any one of claims 21 to 23, wherein the photocurable ink is free of halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.

[0142] EMBODIMENT 25 25. The method of any one of claims 21 to 24, further comprising performing one or more additional surface treatments on the additional major surface of the glass substrate, the one or more additional surface treatments comprising at least one of chemically etching the additional major surface such that the additional major surface exhibits antiglare properties and depositing an antireflective coating on the additional major surface.

[0143] EMBODIMENT 26 26. The method of any one of claims 21 to 25, further comprising depositing a light management layer on the major surface prior to depositing the photocurable ink, the light management layer being made from an ink having a different composition than the photocurable ink and at least partially overlapping the opaque layer. [Explanation of symbols]

[0144] 100, 200, 300 Cabin Systems 110 Center console base 120, 220, 320 curved surface 130, 230, 330, 540 Display 210 Dashboard Base 215 Instrument Panel 310 Dashboard handle base 400 Glass items 450 Substrate 460 Optical Management Layer 470 First main surface 480 Second main surface 490 Functional surface layer 500, 802, 1000 opaque layers 520 display area Tape used in 804 and 1002 tests 902, 904 Crack

Claims

1. a glass substrate having a first major surface and a second major surface opposite the first major surface; and an opaque layer disposed on the second major surface, the opaque layer being made from a photocurable ink including at least 10% by weight pigment; the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater; The opaque layer is cured by exposure to curing light from an ultraviolet ("UV") light emitting diode ("LED") and then A pencil hardness of 3H or greater, as measured in accordance with ASTM 3363; and Adhesion to glass substrates of 4B or greater when measured according to ASTM 3359 after exposure to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours; Indicating an opaque layer, A glass article comprising:

2. 2. The glass article of claim 1, wherein the thickness is 10 μm or less.

3. 3. The glass article of claim 1, wherein the pigment has an average particle size of 200 nm or less.

4. The opaque layer has a resistivity of 1×10 when measured according to ASTM D-257 at 100 V DC. 9 3. The glass article according to claim 1 or 2, which exhibits an electrical resistivity of Ω / □ or more.

5. The glass article has a CIELAB SCI L of 30 or less when illuminated at an angle of 10° by a D65 light source. * When the glass article is illuminated at an angle of 10° by a D65 light source, the glass article has a CIELAB SCI a value of -0.05 or more and 0.15 or less. * value, and CIELAB SCI b value greater than or equal to -0.3 and less than or equal to -0.1 * 3. The glass article of claim 1, wherein the glass article exhibits a value.

6. 3. The glass article of claim 1 or 2, further comprising a light management layer disposed on the second major surface between the glass substrate and the opaque layer, the light management layer being formed from an ink and having an average light transmission of 70% or less from 380 nm to 750 nm.

7. 1. A method of making a glass article, comprising: depositing a photocurable ink onto a major surface of a glass substrate using an inkjet printhead at a deposition temperature of 65° C. or less, wherein during deposition, the photocurable ink has a viscosity of less than 25 cP, and the photocurable ink comprises at least 10% by weight of a pigment and at least 50% by weight of a reactive monomer; and curing the photocurable ink on the major surface to form an opaque layer by exposing the photocurable ink to curing light generated by an ultraviolet ("UV") light emitting diode ("LED"), the curing light having a bandwidth of 30 nm or less; and the opaque layer has a thickness of 25 μm or less and an optical density of 4.0 or greater; The opaque layer is A pencil hardness of 3H or greater, as measured in accordance with ASTM 3363; and A method which exhibits adhesion to a glass substrate of 4B or greater, as measured in accordance with ASTM 3359, when exposed to a temperature of 85° C. at 95% relative humidity for a period of at least 500 hours.

8. The method of claim 7 further comprising priming a major surface of the glass substrate with an acryloxysilane primer prior to depositing the photocurable ink.

9. 9. The method of claim 7 or 8, wherein the opaque layer covers a peripheral portion of the major surface such that the glass article exhibits a higher optical transmission from 380 nm to 750 nm in a central region not including the opaque layer.

10. 9. The method of claim 7 or 8, wherein the photocurable ink is free of halogenated hydrocarbons, ethylbenzene, propylene oxide, styrene, benzene, isopropyl nitrite, butyl nitrite, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether, ethylene glycol formaldehyde acetate, 2-nitropropane, 2-methyl-2-pyrrolidone, triethylene glycol dimethyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, toluene, and xylene.